Enseñanza virtual y su impacto en el proceso de enseñanza aprendizaje de los estudiantes de 5to EGB de la UE “Adolfo María Astudillo” Babahoyo, 2021 - Santillan Cortez, Lady Gardenia (2022)
As a consequence of the pandemic that we are experiencing, the whole world entered a mandatory quarantine and this action brought serious consequences to various sectors of society, and especially to education where children and young people have been the most affected, they spent a few months in Confinement and seeing that the world situation did not improve, the authorities chose to implement strategies so that students do not miss more classes, this strategy was to implement online classes, that is, through a monitor or a Smartphone screen However, although the idea is good, the country is not in adequate conditions to pay the expenses that this decision entails and therefore the inhabitants do not get the most out of it. Both students and teachers are not trained enough to cope with this decision, which has caused teachers not to know how to handle a technological equipment and since they do not train them they incur expenses to hire a person to help them in case they do not have any family to help them, on the other hand, certain families do not have the technological equipment required to face virtual classes or the purchasing power necessary to buy a new equipment. The academic performance as a result of the pandemic has had a drop in grades in most of the students and all agree that the reason comes from the lack of experience with technological equipment of the teachers and the failure or lack of acquisition of educational tools, so they think that, although they are aware of the pandemic that the country is going through, they prefer face-to-face classes over virtual ones, because in the country the teachers are not trained to do so. Management of the platforms necessary for the application of on-line chairs.